Optimal supervisory control of automated manufacturing systems - Chen, Yufeng (Mechanical engineer) (CRC Press, Taylor & Francis Group, 2013)
This monograph presents the state-of-the-art developments in the design of behaviorally and structurally optimal livenessen-forcing Petri net supervisors with computationally tractable approaches. It details optimal supervisory control problems arising in automated production systems and outlines a methodology to achieve the optimality purposes of deadlock prevention via converting a variety of problems under consideration into integer linear programming models. The book includes a reference bibliography at the end of each chapter and a complete index.